Consumption Behaviour of Scholarship Students in Indonesia - Albrian Fiky Prakoso; Tessa Rachmaviani; Ardhita Eko Ginanjar; Arina Salsabilla Haq (Economics Education Department Universitas Negeri Semarang, 2025)
This research aims to evaluate the development of the consumption behavior model for Academic Achievement Scholarship (AAS) grantees in the Faculty of Economics in Indonesia. This research was quantitative. Samples were taken from six major universities in the region, which spanned three major Indonesian islands, and included a total of 238 students from the Faculty of Economics in Indonesia who received the AAS Scholarship. Methods of data collection include the use of questionnaires, which are analyzed using SEM-PLS. The data demonstrated that economic literacy did not affect consumptive behaviour, hedonic conformity exerted a positive and meaningful influence on consumptive behaviour, self-control was found to positively and significantly influence consumptive behaviour, economic literacy and hedonic conformity had a negative and significant effect on self-control, and self-control can mediate the effect of economic literacy on consumptive behaviour. Self-control can also mediate the effect of hedonic conformity on consumptive behaviour. The implication is that self-control mediates the relationship between economic literacy and hedonic conformity in consumptive behavior. This research investigates the mediating role of self-control in the relationship between economic literacy, hedonic conformity, and consumption behavior, thereby contributing to a deeper understanding of the factors influencing consumption patterns among scholarship recipients.